Left Ventricular Intramyocardial Dissecting Hematoma: A Multimodality Imaging Diagnostic Approach. (July 2021) - Alyousef, Tareq; Malhotra, Saurabh; Iskander, Fady; Gomez, Javier; Basu, Anupam; Tottleben, Jonathan; Doukky, Rami
Abstract : Supplemental Digital Content is available in the text.